OFR-11-77 The Correlation Of Mine Roof Failure With The Time Elapse Before Support Installation - Robert M. Cox (The National Institute for Occupational Safety and Health (NIOSH), 1974)
The objective of this study was to determine if significant relationships exist between coal mine roof stability and the time roof is left unsupported. Additional factors such as geology, opening geometry, and mining methods were also studied: to determine their relative influence on mine roof stability. The results of the study indicate that geologic factors such as shear zones (either joints or faults) and changes in roof rock lithology were the principal factors governing mine roof stability. The time lapse factor appeared to be of critical importance when poor mine roof conditions are encountered. The study pointed up the need for improved and permissible rock mechanics instrumentation for use in coal mine investigations.